Lignin Doped Carbon Nanotube Yarns for Improved Thermoelectric Efficiency. (24th September 2020) - Culebras, Mario; Ren, Guang; O'Connell, Steward; Vilatela, Juan J.; Collins, Maurice N.
Abstract: Due to ever increasing public awareness of the deteriorating planetary health condition associated with climate change and increasing carbon emissions, sustainable energy development has come sharply into focus. Here, a thermoelectric material is produced, which consists of macroscopic carbon nanotube yarns (CNTYs) produced continuously from the gas‐phase. The CNTYs are doped with lignin, obtained from lignocellulosic waste, and at 23 wt% lignin, electrical conductivity and the Seebeck coefficient are approximately doubled when compared to pristine CNTY samples. As a consequence, the power factor is remarkably improved to 132.2 µW m −1 K −2, more than six times that of the pristine CNTY. A thermoelectric generator device is manufactured, comprising 20 CNTY/lignin nanocomposite yarns, and they exhibit a maximum power output of 3.8 µW, at a temperature gradient of 30 K. Abstract : Lignin, a sustainable biopolymer and a non‐valorized by‐product of the paper and pulp industry, is capable of tuning the thermoelectric properties of carbon nanotube yarns (CNTY) increasing their thermoelectric efficiency one order of magnitude as the lignin molecules densify the CNTY bundles through strong π–π interactions forming an interconnected network.